2013
DOI: 10.1063/1.4822481
|View full text |Cite
|
Sign up to set email alerts
|

Rapid mixing implies exponential decay of correlations

Abstract: We provide an analysis of the correlation properties of spin and fermionic systems on a lattice evolving according to open system dynamics generated by a local primitive Liouvillian. We show that if the Liouvillian has a spectral gap which is independent of the system size, then the correlations between local observables decay exponentially as a function of the distance between their supports. We prove, furthermore, that if the Log-Sobolev constant is independent of the system size, then the system satisfies c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 48 publications
4
73
0
Order By: Relevance
“…It has also been shown that in 1D exponential clustering of correlations already implies an area law [7]. For local Liouvillians, general area laws (in terms of entropic measures suitable for mixed states) can be derived for stationary states [33], again using Lieb-Robinson bounds.…”
Section: Clustering Of Correlations In Liouvillian Systemsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has also been shown that in 1D exponential clustering of correlations already implies an area law [7]. For local Liouvillians, general area laws (in terms of entropic measures suitable for mixed states) can be derived for stationary states [33], again using Lieb-Robinson bounds.…”
Section: Clustering Of Correlations In Liouvillian Systemsmentioning
confidence: 99%
“…[55] and has been made rigorous and largely generalized in Ref. [33]: If a local Liouvillian is primitive (that is, if its stationary state has full rank) and has a spectral gap which is independent of the system size, then correlation functions between local observables again decay exponentially as a function of the distance between their supports.…”
Section: Clustering Of Correlations In Liouvillian Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Namely, if the gap is finite (so-called rapidly mixing systems) one can show that this implies a clustering of correlations in the steady state [8,9], meaning that local observables are uncorrelated on a scale larger than ∼ 1/g. Rapid mixing also implies the stability of steady state to local perturbations [10][11][12]. If the gap on the other hand closes in the thermodynamic limit this can lead to a nonequilibrium phase transition [13][14][15][16][17][18] and can result in a non-exponential relaxation [19,20] towards a steady state.…”
Section: Introductionmentioning
confidence: 99%